A Identidade Vocal de Luiz Gonzaga e Jackson do Pandeiro em Performance - Laranjeira, Deneil José (2012)
The present work establishes the elements of vocal identity of Luiz Gonzaga and Jackson do Pandeiro. It is based on performance and identity studies, meter concepts, and Alan Merriam s trifold concept of music. Six pieces from different career moments of both artists were transcribed and analyzed in its various technical aspects. Also, aspects of musical formation and life history of each of them were approached in an attempt to understand how aesthetics references contributed to their final sonorities and interpretations. Comparing their choices and musical performance procedures it was possible to establish connections between their performances and the theoretical frame that support this research.